Social and Economic Problems of the Libyan Family in Light of Certain Variables "A Field Study of a Sample of Breadwinner-less Families in the City of Benghazi" - Salima Husayn Eabd Allah Qadribuh (Journal of Libyan Academy Bani Walid, 2025)
This study aims to identify the social and economic problems faced by families who have lost their breadwinner in the city of Benghazi, in light of certain variables, including: gender, age of the head of the family, number of family members, monthly household income, educational level of the head of the family, housing ownership, occupation of the head of the family, and the number of years since the loss of the breadwinner. The study adopted a descriptive approach using the case study method. Data were collected through interview forms, applied to a sample of (50) cases. The study findings revealed that the most prominent social problems faced by families who lost their breadwinner include conflicts with relatives after the death of the family head, disputes with family members over inheritance, reduced participation in social activities following the loss of the breadwinner, and internal family conflicts regarding the management of household affairs. Regarding economic problems, the study found that these families suffer from rising prices, poor financial conditions after the death of the breadwinner, inability to establish income-generating projects to improve their financial situation, and reliance on borrowing to meet the basic needs of family members. In addition, the case studies highlighted several other problems, such as the inability to bear family responsibilities, difficulties in dealing with children, high cost of living, increasing debts, lack of liquidity, delayed salaries, as well as society’s negative perception of female heads of households—especially younger women—and their exposure to exploitation.